Pre and postoperative analgesia for orthopedic surgeries - Kawai, Verônica Ferreira De Aguiar (2015)
ABSTRACT BACKGROUND AND OBJECTIVES: Pain is frequent in wards and impairs patients’ treatment and recovery, especially orthopedic patients. So, this study aimed at evaluating pre and postoperative analgesic adequacy in patients submitted to orthopedic surgeries, and at looking for possible variables predicting the analgesic adequacy of such patients in both moments. METHODS: This is a quasi-experimental study with two groups, orthopedic pre and postoperative periods, carried out through structured interview, physical evaluation and medical record analysis, in the Surgical Clinic of the Teaching Hospital, School of Medicine, Itajuba/MG, developed with patients in the pre and postoperative periods of orthopedic surgery. RESULTS: Participated in the study 31 patients, all of them with medical prescription of some analgesic drug, being weak opioids those most frequently prescribed in 84% of preoperative cases, increasing to 87% in the postoperative period; 39% had no preoperative pain, decreasing to 36% in the postoperative period. On the other hand, 39% of patients had moderate to severe pain in the preoperative period, increasing to 45% in the postoperative period, being that 74% had analgesic adequacy in the preoperative period, increasing to 81% in the postoperative period. CONCLUSION: Most patients of this study had adequate analgesia in the pre and postoperative periods of orthopedic surgery. In our sample, selected variables have not adequately predicted analgesic adequacy in both moments of the orthopedic surgery.